Pengaruh Rasio Likuiditas dan Solvabilitas terhadap ROA pada Perbankan Syariah yang Terdaftar di ISSI - Baihaqi, Muhammad; Asih, Vemy Suci (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
This study analyzes the effect of liquidity ratio, namely Financing to Deposit Ratio (FDR), and solvency ratio, namely Capital Adequacy Ratio (CAR), on the financial performance of Islamic banks listed on the Indonesia Sharia Stock Index (ISSI), focusing on Return on Assets (ROA). Using a quantitative approach and panel regression analysis of data from the financial statements of Islamic banks for the period 2019-2023, the results showed that FDR has a positive and significant effect on ROA, which means that an increase in financing distribution contributes to profitability. In contrast, CAR shows a negative and significant influence on ROA, where too high a level of capital can reduce bank profitability. Simultaneously, FDR and CAR explain 70.38% of the variation in ROA, confirming the importance of balance in liquidity and capital management. This study provides theoretical and practical contributions in the management of financial ratios of Islamic banks, and recommends that Islamic banks increase prudent financing distribution and allocate excess capital for productive activities according to sharia principles.